Pharmacokinetics And Bioequivalence Of Generic Etoricoxib In Healthy Volunteers - Nishalini Harikrishnan; Ka-Liong Tan; Kar Ming Yee; Alia Shaari Ahmad Shukri; Nalla Ramana Reddy; Chuei Wuei Leong (Generics and Biosimilars Initiative (GaBI), 2024)
Indexed by WOS/ Scopus